Efforts to Increase Student Learning Interest from Conventional Learning to the Matching Cards Model at MA Muhammadiyah Pekanbaru - Sundari, Sundari; Yusmak, Rini (Riviera Publishing, 2025)
The quality of education in Indonesia, particularly at the secondary level, faces challenges related to low student engagement and passive learning approaches. Conventional teaching methods often fail to stimulate students' active participation and intrinsic motivation, resulting in decreased learning interest and academic performance. At MA Muhammadiyah Pekanbaru, preliminary observations revealed that students exhibited limited enthusiasm during lessons, minimal peer interaction, and low levels of classroom participation. These conditions indicate the need for innovative pedagogical strategies that can foster more engaging and interactive learning environments. The Matching Cards learning model, as a cooperative learning technique, offers potential solutions by promoting active student involvement through game-based and collaborative activities. This study aims to increase students' learning interest through the application of the Matching Cards learning model as an alternative to conventional learning at MA Muhammadiyah Pekanbaru. Low student learning interest in conventional learning is evident from the lack of active involvement, low learning enthusiasm, and minimal interaction between students. This study used a Classroom Action Research (CAR) approach with two cycles. The results showed that the application of the Matching Cards model had a significant impact on increasing learning interest, marked by increased student activity, enthusiasm, discussion results, and ability to work together.